Evaluación de tres densidades de siembra con seis híbridos del cultivo de Maíz (Zea mays l.), en siembra directa, en San Martín – Perú - Ruiz Reategui, Jorge Luis (2009)
This thesis work was to determine the combination hybrid-density, thus able to obtain optimal performance in the maize crop. This work was performed between July 2008 and in November the same year, the sector Winge, District Picota Picota Province and Department of San Martín. The hybrids used were three triples and three simple, so to prove which of these is better suited to a certain density, and also try other vegetative characteristics of the crop. To achieve the following experiment used a block design with a completely randomized factorial 3 X 6, with 18 treatments and 3 replications per treatment, where the results were analyzed by analysis of variance, Duncan test and the coefficient reliability. Planting is done in a slightly moist soil, using a distance of 0.80 between rows and 0.167m, 0.20m, 0.25m between plants, leaving one plant per desahíje after the coup, thus determining densities of 50 000, 62 500 and 75 000 plants / ha. To improve crop 4 was used for gravity irrigation and fertilization was done using a dose of 180 - 90 - 120 units of NPK, respectively, split into 2 parts, half of the nitrogen, phosphorus and potassium throughout the 16 days of sowing and half of nitrogen to 29 days of sowing. In the result of statistical analysis it was observed that the T9 (hybrid AG-001, with 75,000 plants / ha) was the best performance obtained with an average of 11.24t/ha. The lower performance was the hybrid GA-003 with 50 000 plants / ha, with an average of 8.54t/ha.